A
ankhang1997


1+[TEX]cos^2 x[/TEX]+2cosx.[TEX]cos^2 5x[/TEX]=[TEX]sin^2 5x[/TEX]
[TEX]cos^2 x[/TEX]+2cosx.[TEX]cos^2 5x[/TEX]+[TEX]cos^2 5x[/TEX]=0 (1)
(1) >=[TEX]cos^2 x[/TEX]+2cosx.[TEX]cos^2 5x[/TEX]+[TEX]cos^4 5x[/TEX]=[cosx+(cos5x)^2]^2>=0
rồi giải sao nữa nhờ các bạn giúp cho
[TEX]cos^2 x[/TEX]+2cosx.[TEX]cos^2 5x[/TEX]+[TEX]cos^2 5x[/TEX]=0 (1)
(1) >=[TEX]cos^2 x[/TEX]+2cosx.[TEX]cos^2 5x[/TEX]+[TEX]cos^4 5x[/TEX]=[cosx+(cos5x)^2]^2>=0
rồi giải sao nữa nhờ các bạn giúp cho
Last edited by a moderator: